Simulations and design of a prototype resistive plate chamber - Yıldızcı, Emre Burak. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
Resistive Plate Chambers (RPCs) are particle detectors used by a wide variety of experiments around the world to cover large detection areas as they have good spatial and time resolutions as well as an uncomplicated construction process and are relatively inexpensive. A domestic prototype RPC has been built at KAHVELab and promising preliminary results have been acquired. In this thesis, various aspects of RPC design have been simulated and the results, which are in agreement with the literature, are presented. In addition, basics of muography, an imaging method based on atmospheric muons, are discussed and simulations have been performed for various detection setups both with ideal detectors, to gauge the limitations, and RPCs with varying spatial resolutions. The results suggest that RPCs, even with modest spatial resolutions, can be utilized in absorption muography.
Keywords: Particles (Nuclear physics)